Microfluidic Impedance‐Deformability Cytometry for Label‐Free Single Neutrophil Mechanophenotyping (Small 18/2022). Issue 18 (5th May 2022) - Petchakup, Chayakorn; Yang, Haoning; Gong, Lingyan; He, Linwei; Tay, Hui Min; Dalan, Rinkoo; Chung, Aram J.; Li, King Ho Holden; Hou, Han Wei
Abstract : Neutrophil Mechanophenotyping The intrinsic biophysical states of neutrophils are often associated with immune dysfunctions. In article number 2104822, Han Wei Hou and co‐workers report an "optics‐free" microfluidic biophysical cytometer for impedance‐based single cell electro‐mechano‐phenotyping. The developed platform integrates elasto‐inertial focusing, hydrodynamic cell pinching, and multifrequency differential impedance sensing to enable label‐free and multi‐parametric neutrophil profiling towards rapid clinical diagnostics.